Astrovirus infections induce age-dependent dysbiosis in gut microbiomes of bats. Issue 12 (December 2018) - Wasimuddin,; Brändel, Stefan; Tschapka, Marco; Page, Rachel; Rasche, Andrea; Corman, Victor; Drosten, Christian; Sommer, Simone
Abstract Astroviruses (AstV) are a major cause of diarrhoea in children. Interestingly, some wildlife species, including bats, remain phenotypically asymptomatic after infection. Disease symptoms, however, may only be less visible in bats and enteric viruses may indeed perturb their gut microbial communities. Gut microbiomes represent an important driver of immune defence mechanisms but potential effects of enteric virus-host microbiome interactions are largely unexplored. Using bats as a natural model system, we show that AstV-infections affect the gut microbiome, with the strength of the effect depending on host age. The gut microbial α- and β-diversity and the predicted microbial functional orthologs decreased in young bats but surprisingly increased in adult AstV + bats. The abundance of bacterial taxa characteristic for healthy microbiomes was strongly reduced in young AstV+ bats, possibly attributable to their immature immune system. Regardless of age, pathogen-containing genera exhibited negative interactions with several commensal taxa and increased after AstV-infection, leading to pathobiont-like shifts in the gut microbiome of all infected bats. Thus, in apparently healthy bats, AstV-infections disturb gut bacterial homeostasis, possibly increasing previously suppressed health risks by promoting co-infections. If similar processes are present in humans, the effects of enteric virus infections might have longer-term impacts extending beyond the directly observed symptoms.